2019
DOI: 10.1186/s13000-019-0862-9
|View full text |Cite
|
Sign up to set email alerts
|

Extremely rare case of intravascular solitary fibrous tumour in the inferior vena cava with review of the literature

Abstract: Background Solitary fibrous tumour (SFT) is a mesenchymal tumour of fibroblastic type, and it develops in almost any part of the human body. However, according to previous studies, the occurrence of intravascular SFTs is extremely rare. Case presentation We reported a case of intravascular SFT in a 67-year-old woman who has been experiencing swelling and pain in the right leg for 2 months. Computed tomography venography scan revealed a well-defined mass obstructing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…SFT is a rare type of neoplasm of mesenchymal origin, but especially mostly originated from the submesothelial SFTs are predominantly observed in middle-aged men and women, with no signi icant sex predilection [3]. Nevertheless, most tumors are benign, but minority of cases might have aggressive behaviors, such as local recurrence and metastasis [3]. SFTs has been observed at almost every extra pleural anatomic site, including the liver, kidney, pancreas, prostate and breast [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SFT is a rare type of neoplasm of mesenchymal origin, but especially mostly originated from the submesothelial SFTs are predominantly observed in middle-aged men and women, with no signi icant sex predilection [3]. Nevertheless, most tumors are benign, but minority of cases might have aggressive behaviors, such as local recurrence and metastasis [3]. SFTs has been observed at almost every extra pleural anatomic site, including the liver, kidney, pancreas, prostate and breast [3].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, most tumors are benign, but minority of cases might have aggressive behaviors, such as local recurrence and metastasis [3]. SFTs has been observed at almost every extra pleural anatomic site, including the liver, kidney, pancreas, prostate and breast [3]. Even though video-thoracoscopy approaches were enhanced, still one of the ports had to be enlarged due to size of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also supported the observation that the biological behavior of SFTs is not strictly dependent on tumor size and mitotic count; thus, even SFTs that are considered benign based on histology may aggressively recur. 25 The gold standard treatment for SFTs is surgical resection. 26 Demicco et al 26 analyzed 110 patients with SFTs after surgery and reported that the overall 5-and 10-year patient survival rates were 89% and 73%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also supported the observation that the biological behavior of SFTs is not strictly dependent on tumor size and mitotic count; thus, even SFTs that are considered benign based on histology may aggressively recur. 25…”
Section: Discussionmentioning
confidence: 99%
“…Elucidating the metabolic responses of P. aeruginosa to mucins can enable the development of protective approaches against infection 8 . Genome-scale metabolic network reconstructions (GENREs) and associated genome-scale metabolic models (GEMs) are well suited for this purpose as they can enable the prediction of cellular behavior under different biological conditions such as the absence or presence of different mucins in an environment 9 . A GENRE can also be used to contextualize high-throughput data, such as transcriptomics or proteomics data 10 .…”
Section: Introductionmentioning
confidence: 99%